Frequency effects of L2 English on the processing of the passive in L1 Brazilian Portuguese (Revista de Estudos da Linguagem, 2024)
This study investigated the influence of experience with L2 English in the processing of passives in L1 Brazilian Portuguese (BP) by high-proficiency bilinguals and BP monolinguals. Based on the premise that high L2 proficiency is indicative of widespread representational sharing (BERNOLET; HARTSUIKER; PICKERING, 2013) and on the observation that the passive is significantly more productive in English than in BP (GUIMARÃES; SOUZA, 2016), bilinguals’ processing of the construction is expected to be facilitated by L2 exposure. Subjects performed an acceptability judgment task and two sentence elicitation tasks. Both groups considered the passive as acceptable as the active, with no significant differences between the two groups’ judgments of the passive. Differences were found in the oral production of passives between bilinguals and monolinguals, but not in written production: task type influenced the production of monolinguals in that passive productivity fell significantly from the written to the oral task. The difference in productivity levels of the passive between bilinguals and monolinguals is attributed to bilinguals’ exposure to the construction’s distributional properties in the L2, supporting models of bilingual shared representations (HARTSUIKER; PICKERING; VELTKAMP, 2004).